Fatty acid-binding protein 5 limits ILC2-mediated allergic lung inflammation in a murine asthma model - Kobayashi, Shuhei (Sci Rep, 2020)
Dietary obesity is regarded as a problem worldwide, and it has been revealed the strong linkage between obesity and allergic inflammation. Fatty acid-binding protein 5 (FABP5) is expressed in lung cells, such as alveolar epithelial cells (ECs) and alveolar macrophages, and plays an important role in infectious lung inflammation. However, we do not know precise mechanisms on how lipid metabolic change in the lung affects allergic lung inflammation. In this study, we showed that Fabp5(−/−) mice exhibited a severe symptom of allergic lung inflammation. We sought to examine the role of FABP5 in the allergic lung inflammation and demonstrated that the expression of FABP5 acts as a novel positive regulator of ST2 expression in alveolar ECs to generate retinoic acid (RA) and supports the synthesis of RA from type II alveolar ECs to suppress excessive activation of innate lymphoid cell (ILC) 2 during allergic lung inflammation. Furthermore, high-fat diet (HFD)-fed mice exhibit the downregulation of FABP5 and ST2 expression in the lung tissue compared with normal diet (ND)-fed mice. These phenomena might be the reason why obese people are more susceptible to allergic lung inflammation. Thus, FABP5 is potentially a therapeutic target for treating ILC2-mediated allergic lung inflammation.